ขั้นตอนวิธีสำหรับการสร้างสมมติฐานการวิจัยแบบมีทิศทาง โดยใช้เทคนิคการค้นหาเส้นทางในแนวลึก AN ALGORITHM FOR GENERATING DIRECTIONAL RESEARCH HYPOTHESIS USING DEPTH-FIRST SEARCH TECHNIQUE - หิรัญพงศ์สิน สุภาวดี; สิงห์งาม จิรยุทธ (Srinakharinwirot University Journal of Sciences and Technology, 2021)
The objectives of this research were to develop an algorithm for generating directional research hypothesis using depth-first search technique, named as GHyp which was developed by JavaScript language. This research consisted of five processes that were 1) studied and reviewed the concept of system thinking and related works 2) collected and analyzed information 3) analyzed and designed GHyp 4) developed and tested GHyp, and 5) evaluated the quality of the proposed algorithm. The results of this research found that the GHyp algorithm could correctly generate of all directional research hypothesis according to the expected results. Moreover, the quality of GHyp algorithm assessed by experts found that the Index of the item-objective congruence of expert opinion analysis on every GHyp algorithms was equal to 0.97. Conclusively, GHyp could be practical and could be used as the tool for generating directional research hypothesis, including used as the obvious conceptual research framework. As a result, users had more systematic thinking skills and more hypothesis-building skills.